Damaged hardmen: Organized crime and the half‐life of deindustrialization. (28th February 2021) - Fraser, Alistair; Clark, Andy
Abstract: Despite frequent associations, deindustrialization features rarely in studies of organized crime, and organized crime is at best a spectral presence in studies of deindustrialization. By developing an original application of Linkon's concept of the "half‐life, " we present an empirical case for the symbiotic relationship between former sites of industry and the emergence of criminal markets. Based on a detailed case‐study in the west of Scotland, an area long associated with both industry and crime, the paper interrogates the environmental, social, and cultural after‐effects of deindustrialization at a community level. Drawing on 55 interviews with residents and service‐providers in Tunbrooke, an urban community where an enduring criminal market grew in the ruins of industry, the paper elaborates the complex landscapes of identity, vulnerability, and harm that are embedded in the symbiosis of crime and deindustrialization. Building on recent scholarship, the paper argues that organized crime in Tunbrooke is best understood as an instance of "residual culture" grafted onto a fragmented, volatile criminal marketplace where the stable props of territorial identity are unsettled. The analysis allows for an extension of both the study of deindustrialization and organized crime, appreciating the "enduring legacies" of closure on young people, communal identity, and social relations in the twenty‐first century.